Updated checklist and identification key of benthic tanaidaceans (Crustacea: Peracarida) of the sublittoral zone of the northern Yucatan Peninsula, Mexico - Abarca-Ávila, Mónica Mariel; Herrera-Dorantes, María Teresa; Winfield, Ignacio; Ardisson, Pedro-Luis (Zootaxa, 2019)
A taxonomic checklist of sublittoral tanaidaceans from the north coast of the Yucatan Peninsula, southern Gulf of Mexico, is presented in this study; it includes notes on geographic distribution, habitat, and an identification key. The genus Cacoheterotanais and the species Cacoheterotanais rogerbamberi, Mesokalliapseudes macsweenyi, Pagurotanais largoensis, Parakonarus juliae, and Psammokalliapseudes granulosus have their known distribution range within the Gulf of Mexico expanded, and are considered new records; this increases the number of tanaidacean species to 23 for the southeastern Gulf, and to 87 for the entire Gulf of Mexico.